A Potentiometric Electronic Skin for Thermosensation and Mechanosensation. (22nd February 2021) - Wu, Xiaodong; Zhu, Juan; Evans, James W.; Lu, Canhui; Arias, Ana C.
Abstract: Electronic skins (e‐skins) that mimic the thermosensation and mechanosensation functionalities of natural skin are highly desired for the emerging fields of prosthetics and robotics. Advances in the materials and architecture of e‐skins have been made; nevertheless, sensing mechanism innovations are rarely explored. Here, inspired by the skin sensory behaviors, a single potentiometric sensing scheme for both thermosensation and mechanosensation functionalities are presented. Through careful materials selection, component optimization, and structure configuration, the coupling effect between thermosensation and mechanosensation can be significantly minimized. Such a potentiometric sensing scheme enables one to create a new class of energy‐efficient e‐skin with distinctive characteristics that are highly analogous to those of natural human skin. The e‐skin reported here features ultralow power consumption (at nanowatt level), greatly simplified operation (only voltage output), ultrahigh sensitivity (non‐contact sensing capability), all‐solution‐processing fabrication, and, more importantly, good capability for simultaneous monitoring/mapping of both thermal and mechanical stimulations. In addition to proposing a new sensory mechanism, integration of the dual‐functional e‐skin with a soft robotic gripper for object manipulation is demonstrated. The presented concise yet efficient sensing scheme for both thermosensation and mechanosensation opens up previously unexplored avenues for the future design of skin prosthetics, humanoid robotics, and wearable electronics. Abstract : A novel e‐skin for both thermosensation and mechanosensation based on a single potentiometric sensing mechanism is reported. Such potentiometric e‐skin features ultralow power consumption, greatly simplified operation, all‐solution‐processing fabrication, and good capability for simultaneous mapping of both thermal and mechanical stimulations. This innovative sensing scheme provides a concise yet efficient design philosophy for future skin prosthetics and humanoid robotics.